Directive Speech Act Performed by Male and Female Speakers’ in Ted Talk Language Learning Videos - Husnan, Donni; Kustanti, Dewi; Fauzi, Erfan Muhammad (Universitas Galuh, 2025)
This study analyzes the use of directive speech acts in TED Talk language learning videos through a pragmatic approach, focusing on orders and suggestions as primary categories. The research examines the speeches of four speakers Matyas Pilin, Chris Lonsdale Lydia Machova, and Marianna Pascal to understand how their speech styles influence the delivery of language learning strategies. This research employed a descriptive qualitative method with purposive sampling data collection. From the 273 data that the author found, 47 data of utterances were selected from four different videos for analysis. The findings reveal that male speakers predominantly use orders, emphasizing a structured and authoritative instructional approach, while female speakers favor suggestions, promoting a supportive and motivational teaching style. This balance between orders and suggestions highlights the diverse strategies employed to address both cognitive and emotional aspects of learners. This study contributes to the fields of pragmatics and educational communication by demonstrating how directive speech acts influence instructional effectiveness. The findings provide valuable insights for educators, linguists, and public speakers in developing more impactful and learner-centered teaching methods. Moreover, the study offers a foundation for further research into the interplay of speech acts, instructional strategies, and cultural or contextual influences in educational settings.